What drives firm profitability? A multilevel approach to the Spanish agri-food sector - Ferdaous Zouaghi; Mercedes Sánchez-García; Stefan Hirsch (Spanish Journal of Agricultural Research, 2017)
Strategic management research has demonstrated the importance of firm- and industry structure as drivers of firm profitability. However, less is known about how firms´ geographical locations affect profitability. Applying a multi-level approach of hierarchical linear modeling we estimated firm-, industry-, and region-specific effects on profitability of 3,273 agri-food firms operating in different Spanish districts over the time span 2006-2013. The results reveal the dominance of firm-specific effects which contribute up to 48.8% to variance in firm profitability while the contribution of industry effects (0.8-4.2%), geographical location (0.1-1.8%), and year effects (0.1-2.5%) is rather small. Moreover, firm size, risk, and innovative activity turn out as significant profit drivers at the firm level. Although firm-effects outweigh industry- and region-specific factors, the results indicate that industry concentration as well as regional education and unemployment influence profitability. In addition, proximity to technological institutes as well as the degree of urbanization of the region in which a firm operates can be drivers of profitability. Hence, despite the superiority of firm effects the results indicate that agri-food managers should also consider possible advantages from location-based resources in order to ensure competitiveness.